Precision Public Health for Non-communicable Diseases: An Emerging Strategic Roadmap and Multinational Use Cases - Canfell, Oliver J.; Davidson, Kamila; Woods, Leanna; Sullivan, Clair; Cocoros, Noelle M.; Klompas, Michael; Zambarano, Bob; Eakin, Elizabeth; Littlewood, Robyn; Burton-Jones, Andrew (Frontiers in Public Health, 2022)
Non-communicable diseases (NCDs) remain the largest global public health threat. The emerging field of precision public health (PPH) offers a transformative opportunity to capitalize on digital health data to create an agile, responsive and data-driven public health system to actively prevent NCDs. Using learnings from digital health, our aim is to propose a vision toward PPH for NCDs across three horizons of digital health transformation: Horizon 1—digital public health workflows; Horizon 2—population health data and analytics; Horizon 3—precision public health. This perspective provides a high-level strategic roadmap for public health practitioners and policymakers, health system stakeholders and researchers to achieving PPH for NCDs. Two multinational use cases are presented to contextualize our roadmap in pragmatic action: ESP and RiskScape (USA), a mature PPH platform for multiple NCDs, and PopHQ (Australia), a proof-of-concept population health informatics tool to monitor and prevent obesity. Our intent is to provide a strategic foundation to guide new health policy, investment and research in the rapidly emerging but nascent area of PPH to reduce the public health burden of NCDs.